SOCIAL WORK IN COMON PRACTICE OF REPUBLIC OF SRPSKA SOCIAL PROTECTION - Cuk, Mira; Savović, Irina (Politeia, 2019)
The review presents the results of a qualitative research conducted with the assistance of thirteen  social workers employed in social care institutions. The purpose of the research is to determine their attitudes on the issues of social work in social protection in present-day conditions. The focus group method is used for data collection and the method of frame analysis is used in setting up research questions and analysing the findings. The results of the research show that there is a routine present in the jobs of social workers in  social welfare institutions, with few changes introduced, with practices including individuals or families being dominant ones. In addition, in most cases changes refer to the establishment of new legal solutions that produce changes in the organisation of labour, whereas social work itself does not affect changes in legislation, with political factors strongly influencing overall social work activities. Furthermore, the results of the research show that social work based on human rights is mostly realised in the domain of individual satisfaction of the needs of users, and that administrative and administrative-legal affairs dominate in practice, while the tasks of monitoring social needs, analysing the situation, starting initiatives, planning and development, and making reports and analyses are completely ignored. Modern challenges that social workers are faced with pose demands that they cannot fully respond to. The right and the obligation to continuous improvement is not a systemically regulated issue, and the lack of support at the level of institutions and social protection systems demotivates them and prevents them in their professional development.
Keywords: Social work; social protection; changes; human rights